Changes in electoral advertising and the effects on competition and participation in Brazilian local elections between 2008 and 2016 - Cervi, Emerson U. (2021)
This paper presents a proposal for measuring the participation and competition in Brazilian local elections, using the Tatu Vanhanen’s Democratization Index, for whom competition and participation are fundamental to analyze democracy in an election. Aggregated data on results of Brazilian local elections between 2008 and 2016 are used in association with the traditional (radio/TV) and digital communication structure in the cities. The hypothesis is that there is an association between intensity of communication and electoral participation. The objective is to analyze how the structure of communication of the electoral advertising affects the participation and competition of the elections, in a time in which there were changes in the electoral laws and a decrease in the traditional communication space. The question guiding the work is: does the visibility of elections caused by changes in electoral rules decrease electoral democracy in these cities? The results show that there are effects in opposite directions.